The velveteen rabbit all you need to do is believe - Landon, Michael, 1964-; Seymour, Jane, 1951-; Skerritt, Tom.; Burstyn, Ellen, 1932-; Anchor Bay Entertainment, Inc. ([United States] : Anchor Bay Entertainment, 2008)
A courageous velveteen rabbit with dreams of becoming a real rabbit someday helps a young boy to win the affections of his strict grandmother and unapproachable father.
Title from container.
Widescreen.
Inspired by the book by Margery Williams.
Special features: Includes cast interviews and deleted scenes.
Voices: Jane Seymour, Tom Skerritt, Ellen Burstyn.
Rating: G.
Keywords: Stuffed animals (Toys) -- Juvenile films; Rabbits -- Juvenile films; Toys -- Juvenile films; Children's films; Films for the hearing impaired